2014
DOI: 10.3389/fphys.2014.00354
|View full text |Cite
|
Sign up to set email alerts
|

Muscle acellular scaffold as a biomaterial: effects on C2C12 cell differentiation and interaction with the murine host environment

Abstract: The extracellular matrix (ECM) of decellularized organs possesses the characteristics of the ideal tissue-engineering scaffold (i.e., histocompatibility, porosity, degradability, non-toxicity). We previously observed that the muscle acellular scaffold (MAS) is a pro-myogenic environment in vivo. In order to determine whether MAS, which is basically muscle ECM, behaves as a myogenic environment, regardless of its location, we analyzed MAS interaction with both muscle and non-muscle cells and tissues, to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…The effects of muscle ECM scaffolds may however not dominate over soluble differentiation cues. Perniconi et al observed that although mouse muscle ECM can provide the necessary cues for differentiation along a muscle lineage, it does not prevent differentiation to other lineages when cells are exposed to specific growth factors [83]. While some of these results are promising, further research is still needed on decellularized skeletal muscle materials for tissue engineering.…”
Section: Ecm Effects On Cell Differentiationmentioning
confidence: 99%
“…The effects of muscle ECM scaffolds may however not dominate over soluble differentiation cues. Perniconi et al observed that although mouse muscle ECM can provide the necessary cues for differentiation along a muscle lineage, it does not prevent differentiation to other lineages when cells are exposed to specific growth factors [83]. While some of these results are promising, further research is still needed on decellularized skeletal muscle materials for tissue engineering.…”
Section: Ecm Effects On Cell Differentiationmentioning
confidence: 99%
“…3 Therefore, the comparability between two or more materials is an important prerequisite to clearly define the characteristics of the investigated materials. In recent years, regenerative medicine issues have stimulated research to investigate an elevated number of new biomatrices 4 aimed at improving tissue healing; in this light, the old concept of bioscaffolds has given way to new concepts, such as acellular scaffolds, 5 cell niche, and cell commitment. [6][7][8][9][10] Regarding the scaffolds, the exposed surface area and porosity play major roles in the proliferative response of cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Existem diversos tipos de biomateriais utilizados na medicina regenerativa, como os biomateriais naturais (biológicos), os quais podem ser derivados de fonte autóloga, alogênica ou xenogênica, e biomateriais sintéticos ou uma mistura dos dois tipos, chamados de biomateriais híbridos . Os biomateriais devem apresentar, como característica, histocompatibilidade, bioatividade, mínima citotoxicidade e ser reabsorvível por processo de biodegradação, restabelecendo o nicho, permitindo a adesão, sobrevivência e diferenciação celular e exercendo influências mecânicas e biológicas no tecido (JONG et al, 2014;PERNICONI et al, 2014).…”
Section: Capítulo 1: Introdução Capítulo 1: Introduçãounclassified